Virus-induced secondary bacterial infection: a concise review - Hendaus MA; Jomha FA; Alhammadi AH (Dove Medical Press, 2015)
Mohamed A Hendaus,1 Fatima A Jomha,2 Ahmed H Alhammadi3 1Department of Pediatrics, Academic General Pediatrics Division, Weill-Cornell Medical College, Hamad Medical Corporation, Doha, Qatar; 2School of Pharmacy, Lebanese International University, Khiara, Lebanon; 3Department of Pediatrics, Academic General Pediatrics Division, Weill-Cornell Medical College, Hamad Medical Corporation, Doha, Qatar Abstract: Respiratory diseases are a very common source of morbidity and mortality among children. Health care providers often face a dilemma when encountering a febrile infant or child with respiratory tract infection. The reason expressed by many clinicians is the trouble to confirm whether the fever is caused by a virus or a bacterium. The aim of this review is to update the current evidence on the virus-induced bacterial infection. We present several clinical as well in vitro studies that support the correlation between virus and secondary bacterial infections. In addition, we discuss the pathophysiology and prevention modes of the virus–bacterium coexistence. A search of the PubMed and MEDLINE databases was carried out for published articles covering bacterial infections associated with respiratory viruses. This review should provide clinicians with a comprehensive idea of the range of bacterial and viral coinfections or secondary infections that could present with viral respiratory illness. Keywords: bacteria, infection, risk, virus